Diurnal evolution of the hourly diffuse solar radiation incident on tilted surfaces in Southeast of Brazil - Souza, Adilson Pacheco de; Escobedo, João Francisco [UNESP] (My University, 2013)
Evaluation has been made on the monthly and annual average diurnal evolution of the hourly diffuse radiation as well as its radiometric fractions on surfaces inclined at 12.85, 22.85 and 32.85° to face North, in climate conditions of Botucatu, São Paulo, Brazil (22.85° S and 48.43° W). Measurements were made between 04/1998 to 08/2001 for 22.85°; 09/2001 to 02/2003 for 12.85° and 01/2004 to 12/2007 for 32.85°, with concomitant measures in the horizontal. For all surfaces the diffuse radiation was obtained from different method. Assessment has been performed as well on the radiometric fractions obtained from the ratio of diffuse radiation and global radiation (KDH and KDβ) and between radiation and diffuse radiation at the top of the atmosphere (KʹDH and KʹDβ) for the horizontal and tilted surfaces in hourly partition. The diffuse radiation levels were dependent on variations in precipitation and cloudiness. There was an increase in the differences between the diffuse radiation and the radiometric fractions with the increment of the angle, and in horizontally, which affected higher levels of diffuse radiation in spring and summer. The values of KDH and KDβ present in an inverse behavior were compared to diffuse radiation and theydecreased in the southern passage due to the increase of the direct component in the total of incident radiation.
Keywords: Solar radiation; Solar energy; Atmospheric transmissivity; Radiometric fractions